Report of the Working Group on Minor Irrigation for Formulation of the Eighth Plan (1990-95) Proposals Constituted By Planning Commission - Planning Commission (Planning Commission, 1989)
During VII Plan, targets of creating additional irrigation potential of 8.6 m. ha. and utilization of potential of 7.00 m. ha. are likely to be achieved.
Government of India Ministry of Water Resources
Minor Irrigation Division